Same-Sex Marriage for Lesbians, Gays, Bisexuals, and Transgenders - Dian ES.; Michael SP.; Bramansya P.; Luigi H. (Hang Tuah Law Journal, 2017)
People This study aimed to investigate a phenomena of lesbian, gay, bisexual, and transgender in Indonesia and analyze the appropriate implementation of legal sentences for both the registry officials of same-sex marriage and the subjects under the Revision of Marriage Law. It used juridical-normative method with statute (problems were analyzed based on the current applied laws) and conceptual approaches (problems were analyzed based on the perspectives of legal experts in many literatures). It brought two results. First, the marriage registry officials carrying on same-sex marriages would be sentenced by 7 years in prison or fine with Category IV Rp 300.000.000 at most. Second, the subjects of same-sex marriage with identity falsification would be sentenced by 12 years in prison or fine with Category V Rp 1.200.000.000.